#ModiWithAkshay: 'Brand Modi', social media and Bollywood star power. Issue 2 (3rd April 2021) - Mitra, Sreya
ABSTRACT: On 24 April 2019, the New Delhi-based news agency, ANI, telecasted a 'non-political' interview of Prime Minister Narendra Modi conducted by Bollywood star Akshay Kumar. Regarded as a PR coup, particularly in the context of the ongoing Indian parliamentary elections, the 'freewheeling' interview underlined Bollywood's increasing proximity with the Modi-led BJP government. Employing a detailed analysis of the interview and the subsequent controversy, I examine the Bollywood star's role in disseminating political rhetoric, underlining in the process both shifts in discourses of Hindi film stardom, as well as the increasing politicisation of the new media ecology. In doing so, I also highlight the long-standing relationship and presence of Hindi film stars in the political arena, a fact that has received scant scholarly attention. As social networking sites like Twitter are inundated with selfies of Bollywood stars with Prime Minister Narendra Modi and hashtags like #CelebritieswithNamo and #ModiWithAkshay, it is imperative to analyse this emergent confluence of the political and the popular. Thus, using the Akshay Kumar–Narendra Modi interview as a case study, I examine not only the relationship between Hindi film stars and politics but also, the role of social media in shaping the current dynamics.